2007
DOI: 10.1002/adsc.200700074
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Enoate Reductases and their Potential Use for Biotransformations

Abstract: Enoate reductases (ERs) selectively reduce carbon-carbon double bonds in a,b-unsaturated carbonyl compounds and thus can be employed to prepare enantiomerically pure aldehydes, ketones, and esters. Most known ERs, most notably Old Yellow Enzyme (OYE), are biochemically very well characterized. Some ERs have only been used in whole-cell systems, with endogenous ketoreductases often interfering with the ER activity. Not many ERs are biocatalytically characterized as to specificity and stability. Here, we cloned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
80
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(82 citation statements)
references
References 43 publications
1
80
0
1
Order By: Relevance
“…Investigation of the carboxylation reaction of Ccr showed that CO 2 and not HCO 3 Ϫ is the carboxylating species. In principle, CO 2 can serve as electrophile in COC forming reactions on negatively polarized (or inverted) carbon atoms (5), whereas HCO 3 Ϫ is a nucleophile that has to be transformed into the carboxylating species by formation of a reactive carboxyphosphate upon ATP/phosphoester hydrolysis or as carboxyl-biotin to serve in enzymatic carboxylation reactions (44,45).…”
Section: General Pattern Of Stereospecificity For Enoyl-(thioester) Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigation of the carboxylation reaction of Ccr showed that CO 2 and not HCO 3 Ϫ is the carboxylating species. In principle, CO 2 can serve as electrophile in COC forming reactions on negatively polarized (or inverted) carbon atoms (5), whereas HCO 3 Ϫ is a nucleophile that has to be transformed into the carboxylating species by formation of a reactive carboxyphosphate upon ATP/phosphoester hydrolysis or as carboxyl-biotin to serve in enzymatic carboxylation reactions (44,45).…”
Section: General Pattern Of Stereospecificity For Enoyl-(thioester) Rmentioning
confidence: 99%
“…Enoate reductases are unique in their ability to reduce selectively CAC bonds in ␣,␤-unsaturated carbonyl compounds and to create thereby up to 2 stereogenic centers in the target molecule. This chemo-and stereoselectivity makes enoate reductases an important addition to the synthetic toolbox (1)(2)(3)(4).…”
mentioning
confidence: 99%
“…Product formation could only be detected when the reaction was catalyzed with whole cells of recombinant E. coli expressing Achr-OYE4 (with E. coli cells harboring the empty vector as a control), suggesting possible deactivation of these substrates toward the purified enzyme. A previous report has indicated that the substrate plays a more important role in the deactivation of enoate reductase than oxygen or elevated temperature (Chaparro-Riggers et al 2007). In an attempt to eliminate the toxicity of the substrate, we tested biphasic systems that contain organic solvent with different partition coefficients.…”
Section: Discussionmentioning
confidence: 99%
“…Most characterized enoate reductases prefer NADPH over NADH as the cofactor (Chaparro-Riggers et al 2007;Toogood et al 2010), whereas only a few prefer NADH (Brige et al 2006;French and Bruce 1994), such as morphinone reductase, SYE1, and SYE3. In the present study, Achr-OYE4 displayed a preference for NADH on using all testing substrates, and the catalytic efficiency toward NADH Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, substrates 1-3a possess two activating groups (carbonyl groups) and they were also readily reduced by members of OYE family. [1] By contrast, other cyclohexanone derivatives 4-7a, which possess only one carbonyl group, had k cat /K m two orders of magnitude lower, despite being structurally similar to ketoisophorone 3a (Table 1, entries 4-8 vs. entry 3). In general, ketones 4-8a and 13a were relatively poor substrates under steady-state conditions (Table 1), whereas aldehydes 9-13a were reduced readily by PETNR.…”
Section: Introductionmentioning
confidence: 94%